Academic production of teachers in the context of the national assessment system for brazilian higher education (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2017)
In the context of the National Higher Education Assessment System (SINAES), Brazilian Higher Education Institutions (IES) live a paradox that involves the research and academic production of teachers. The demand for research in institutional evaluations falls only on the universities. However, in the evaluations of the educational program, the production of teachers is required, regardless of the type of HEI to which the program is linked. This article is based on a broader research that is part of the author's doctoral thesis and aims to present and discuss the legal basis to which it deals with research and academic production in Brazilian HEI, as well as raise the discussion of possible improvements for the improvement of the SINAES. The main laws that regulate Brazilian Higher Education and the aspects related to academic research were studied. It was possible to demonstrate that the current legislation promotes an inconsistency between the organizational distinction of the HEIs and the indicators established in the evaluation instruments of the SINAES. As well as, it became evident that the current configuration of the system discourages the academic production of professors in graduation and favors so that there is a separation of teaching and research, making it necessary the discussion of prompts that can at least minimize these impacts . In this way, it seeks to contribute to the debates about the improvement of the SINAES and for the evaluation of the research activity in the graduation in all types of HEIs.
Keywords: academic production; research; higher education; accreditation; evaluation